2013
DOI: 10.7860/jcdr/2013/6681.3765
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum L-fucose Glycoprotein as Cancer Biomarker in Head and Neck Malignancies without Distant Metastasis

Abstract: Background: Head and neck neoplasia is a major form of cancer in India, accounting for 30% of all cancers which occur in males and 11% of cancers which occur in females. Elevated serum L-fucose glycoprotein levels have been reported to be associated with neoplastic conditions involving various sites. Therefore, monitoring serum/tissue L-fucose glycoprotein levels could be a promising approach for the early diagnosis and prognosis of head neck cancers.Aim: This study was carried out to determine the significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In Table 3, we summarize findings from studies comparing serum fucose and fucosylated glycan profiles from healthy individuals vs. breast, oral/head and neck, HCC, ovarian, CRC, pancreatic, lung and prostate cancer patients. Several of these studies suggest diagnostic potential for serum L-fucose levels, which have been found to be elevated in cancer patient sera in breast [53,54,55], oral/head and neck [56,57,58,59,60,61], HCC [62,63,64,65], CRC [66,67], and ovarian [55,68] cancer patients compared with healthy individuals. Specific fucosylated glycoconjugates have been found to also have potential diagnostic utility.…”
Section: Serum Fucose and Fucosylated Glycoconjugatesmentioning
confidence: 99%
“…In Table 3, we summarize findings from studies comparing serum fucose and fucosylated glycan profiles from healthy individuals vs. breast, oral/head and neck, HCC, ovarian, CRC, pancreatic, lung and prostate cancer patients. Several of these studies suggest diagnostic potential for serum L-fucose levels, which have been found to be elevated in cancer patient sera in breast [53,54,55], oral/head and neck [56,57,58,59,60,61], HCC [62,63,64,65], CRC [66,67], and ovarian [55,68] cancer patients compared with healthy individuals. Specific fucosylated glycoconjugates have been found to also have potential diagnostic utility.…”
Section: Serum Fucose and Fucosylated Glycoconjugatesmentioning
confidence: 99%
“…Although metastasis accounts for about 90% of cancer-related mortality, the molecular mechanism of tumor metastasis is still poorly understood [14]. Migration, invasion, and adhesion of tumor cells are important steps in the process of tumor metastasis [57]. In order to investigate whether Orai1 can be involved in regulating the metastasis of osteosarcoma cells, we used Orai1 siRNAs to successfully silence the expression of Orai1 in MG-63 osteosarcoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor cell metastasis includes invasion into surrounding tissues, infiltration into circulation, migration, and survival in distant organs. Although metastasis accounts for about 90% of cancer-related mortality, the molecular mechanism of tumor metastasis is still poorly understood [57]. Migration, invasion, and adhesion of tumor cells run through the whole process of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a negative correlation between serum fucose levels and histopathological tumor differentiation in our study as well as in the literatures. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%